Studi mutu pelayanan berdasarkan kepuasan pasien di Klinik Gigi dan Mulut RSUP Dr. Wahidin Sudirohusodo Makassar - A. St. Asmidar Anas; Andi Zulkifli Abdullah (DiscoverSys Inc., 2008)
The improvement of quality health service has become a national and global mainissue in the health development. This is due to great demand of service in healthorganization to provide optimum service health. The effort of improving qualityhealth service consists of health organization and health professionals. This studyaimed to describe patient satisfaction of service quality of health professional indental clinic of RSUP Dr. Wahidin Sudirohusodo Makassar. The samples of thisdescriptive survey study were patients of the hospital who fulfill criteria ofinclusion. Intake of samples by purpose, and sample size was 85 people. Patientsatisfaction was determined using RATER dimensions -reliability, assurance,tangible, empathy and responsiveness. Service quality, which was assessed basedon average of percentage of patient answers, is considered good if satisfaction is â‰¥60% and bad if satisfaction is â‰¤ 60%. The results show that the reliability,assurance, tangible, empathy, and responsiveness of health officer, are 82.4%,76.5%, 89.4%, 87.1%, and 78.8% respectively. The study concludes that servicequality of the dental clinic in 2007 was good.